Rapidly Progressive Lactic Acidosis in Patients with Flufenoxuron Poisoning. Issue 3 (May 2014) - Jeong, HH; Yeom, SR; Han, SK; Park, SW
Flufenoxuron is an insect growth regulator which inhibits chitin (exoskeleton) biosynthesis in insect's body. Not much is known about its toxicity to human. This report describes three patients who developed worsening lactic acidosis and hypotension after ingestion of flufenoxuron-containing materials. Two of the three patients received continuous renal replacement therapy and survived. (Hong Kong j.emerg.med. 2014;21:181-184)